Identifying life-history patterns along the fast-slow continuum of mammalian viral carriers - Tonelli, Andrea; Cáceres Escobar, Hernán Guillermo.; Blagrove, Marcus S. C.; Wardeh, Maya; Di Marco, Moreno (Royal Society Publishing, 2024)
Life-history traits have been identified as major indicators of mammals' susceptibility and exposure to viruses due to evolutionary constraints that link life-history speed with species' ecology and immunity. Nonetheless, it is unclear where along the fast-slow continuum of mammalian life-history lies the greatest diversity of host species. Consequently, life-history patterns that govern host-virus associations remain largely unknown. Here we analyse the virome of 1350 wild mammals and detect the characteristics that drive species' compatibility with different groups of viruses. We highlight that mammals with larger body size and either very rapid or very slow life histories are more likely to carry different groups of viruses, particularly zoonotic ones. While some common life-history patterns emerge across carriers, eco-evolutionary characteristics of viral groups appear to determine association with certain carrier species. Our findings underline the importance of incorporating both mammals' life-history information and viruses' ecological diversity into surveillance strategies to identify potential zoonotic carriers in wildlife.
Keywords: Disease ecology; Life-history; Virus; Zoonosis; Ecología